Investment Property: Accounting Practices and Disclosure - Acaranupong, Kittima (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
Thai Accounting Standard 40 (revised 2009) Investment Property has defined investment property as property held to earn rentals or for capital appreciation or both. An investment property shall be measured initially at its cost. For the measurement after initial recognition, an entity may choose either the fair value model or the cost model for all investment property. The effect of adopting Thai Accounting Standard 40 (revised 2009) is that an entity should transfer investment property, which used to be included in Property, Plant and Equipment account, into the “Investment Property” account separately. If an entity chooses the fair value model, the investment property shall be presented as fair value. A gain or loss arising from a change in fair value of investment property shall be recognized in profit and loss for the period when it occurs. If an entity chooses the cost model, the investment property shall be presented as cost less accumulated depreciation less accumulated impairment loss (if any). The accounting policies of companies in the property development sector listed on the Stock Exchange of Thailand in 2012 are investigated in this paper. The results indicate that 84% of companies, which have investment property in their Statement of Financial Position, choose the cost model. The cost model has advantages over fair value model in terms of reliability. However, the fair value model helps the information in the financial statement reflect a more current financial position and performance than that of the cost model. That is, financial information has qualitative characteristics in term of relevance. The disclosure criteria for investment property are that an entity shall disclose whether it has applied the fair value model or the cost model. If an entity applied the cost model, it shall disclose the fair value of investment property in the note to financial statements.